DEVELOPMENT OF HISTORY E-BOOKS BASED ON HISTORICAL HERITAGE IN ROKAN HILIR TO IMPROVE LEARNING MOTIVATION OF GRADE XI STUDENTS AT SMAN 1 KUBU BABUSSALAM: PENGEMBANGAN E-BOOK SEJARAH BERBASIS PENINGGALAN SEJARAH DI ROKAN HILIR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI DI SMAN 1 KUBU BABUSSALAM - Adia Pratama; Ahmal; Asril (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to develop a history e-book based on historical heritage in Rokan Hilir as an innovative learning media to improve students’ learning motivation in history subject for Grade XI at SMAN 1 Kubu Babussalam. The background of this study is the low student engagement in history learning caused by the lack of contextual and interactive teaching materials. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included expert validation, student response questionnaires, and motivation assessment before and after using the developed e-book. The results showed that the e-book was categorized as